In silico evaluation of some 4-(quinolin-2-yl)pyrimidin-2-amine derivatives as potent V600E-BRAF inhibitors with pharmacokinetics ADMET and drug-likeness predictions - Abdullahi Bello Umar; Adamu Uzairu; Gideon Adamu Shallangwa; Sani Uba (SpringerOpen, 2020)
Abstract Background The resistance of V600E-BRAF to the vemurafenib and the side effects of the identified inhibitors trigger the research for a novel and more potent anti-melanoma agents. In this study, virtual docking screening along with pharmacokinetics ADMET and drug-likeness predictions were combined to evaluate some 4-(quinolin-2-yl)pyrimidin-2-amine derivatives as potent V600E-BRAF inhibitors. Results Some of the selected compounds exhibited better binding scores and favorable interaction with the V600E-BRAF enzyme. Out of the screened compounds, two most potent (5 and 9) having good Rerank scores (− 128.011 and − 126.258) emerged as effective and potent V600E-BRAF inhibitors that outperformed the FDA-approved V600E-BRAF inhibitor (vemurafenib, − 118.607). Thus, the molecular docking studies revealed that the studied compounds showed competing for inhibition of V600E-BRAF with vemurafenib at the binding site and possessed better pharmacological parameters based on the drug-likeness rules filters for the oral bioavailability, and ADMET risk parameters. Conclusion The docking analysis, drug-likeness rules filters, and ADMET study identified compounds (5 and 9) as the best hits against V600E-BRAF kinase with enhanced pharmacological properties. This recommends that these compounds may be developed as potent anti-melanoma agents.